Lower levels of oxidative DNA damage and apoptosis in lymphocytes from patients undergoing surgery with propofol anesthesia - Braz, Mariana Gobbo [UNESP]; Braz, Leandro Gobbo [UNESP]; Mazoti, Marina A. [UNESP]; Pinotti, Matheus F. [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Wiley-Blackwell, 2012)
Propofol, which is widely used as an intravenous anesthetic, has a phenolic structure similar to that of a-tocopherol with antioxidant properties that could prevent genotoxicity and cytotoxicity in lymphocytes of anesthetized patients. The aims of this study were to evaluate oxidative DNA damage and apoptosis in lymphocytes and the expression of DNA repair genes in blood cells from patients undergoing elective surgery under anesthesia with propofol. Twenty healthy adults of both genders (1850 years old) who were scheduled for otorhinological surgery were enrolled in this study. Blood samples were collected before anesthesia induction (T1-baseline), 120 min after anesthesia induction (T2), and on the first postoperative day (T3). Oxidative DNA damage in peripheral lymphocytes was assessed using the comet assay. Lymphocytes were phenotyped as T helper or cytotoxic T cells, and apoptosis was evaluated using flow cytometry. The expression of DNA repair genes (hOGG1 and XRCC1) was assessed by quantitative polymerase chain reaction. A reduction in the level of oxidized purines in DNA (P < 0.01) was observed 120 min after anesthesia induction, and reduced apoptosis of T helper cells was observed 120 min after anesthesia induction and on the first postoperative day. Down-regulation of hOGG1 and XRCC1 gene expression was observed on the first postoperative day. In conclusion, patients undergoing non-invasive surgery under propofol anesthesia presented lower levels of oxidized purines and apoptosis of T helper lymphocytes. Furthermore, anesthesia with propofol did not directly influence the expression of the DNA repair genes hOGG1 and XRCC1 in blood cells. (C) Environ. Mol. Mutagen. 2012. Published 2011 Wiley Periodicals, Inc.
Keywords: comet assay; oxidative stress; apoptosis; DNA repair; intravenous anesthetic